2011
DOI: 10.1017/s1355617711001068
|View full text |Cite
|
Sign up to set email alerts
|

Apathy and Depression: Separate Factors in Parkinson's Disease

Abstract: The objective of this study was to test the hypothesis that apathy and depression are dissociable in Parkinson disease (PD) by conducting a confirmatory factor analysis (CFA) of items from two commonly used mood scales. A total of 161 non-demented PD patients (age = 64.1; ± 8.4 years) were administered the Apathy Scale and the Beck Depression Inventory-II. Items were hypothesized to load onto four factors: (1) an apathy factor representing loss of motivation, (2) dysphoric mood factor representing sadness and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
107
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 121 publications
(121 citation statements)
references
References 45 publications
10
107
0
1
Order By: Relevance
“…Our finding dovetails with other reports which show that apathy can be dissociated from depression in PD. Apathy frequently occurs in the absence of depression10, and factor analyses have revealed that the two represent discrete constructs 10. The findings presented here go further by highlighting the importance of considering the multidimensional nature of apathy when assessing relationships with depression.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Our finding dovetails with other reports which show that apathy can be dissociated from depression in PD. Apathy frequently occurs in the absence of depression10, and factor analyses have revealed that the two represent discrete constructs 10. The findings presented here go further by highlighting the importance of considering the multidimensional nature of apathy when assessing relationships with depression.…”
Section: Discussionsupporting
confidence: 59%
“…However, in healthy controls, those who were more emotionally apathetic actually tended to be less depressed. Our finding that depression is negatively associated with ES in healthy controls but not in PD adds to existing studies regarding complex associations between apathy and depression 10. Importantly, this result suggests that different clinical approaches toward apathy in patients with PD compared to the general population might be needed 24.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The total score ranges from 0 to 63, with higher scores reflecting greater depression. Recently, Kirsch-Darrow et al (2011) proposed a "factor-based" scoring of the BDI-II that disentangles symptoms related to apathy (loss of interest/pleasure factor), depression (dysphoric mood factor) and somatic complaints (somatic factor). In our study, we used this factor structure in order to have a "pure" measure of depression that did not overlap with apathy components.…”
Section: Apathy and Clinical Measuresmentioning
confidence: 99%
“…Thus, the Benjamini-Hochberg-Yekutieli correction exerts a less stringent control over false discovery than familywise error rate procedures (such as the Bonferroni correction) and improves power to some extent (Narum, 2006). Finally, to control the influence of other factors not specifically related to depression and nonetheless measured by classical clinical inventories such as the BDI-II, we used the factor analysis of the BDI-II proposed by Kirsch-Darrow et al (2011).…”
Section: Statistical Analysesmentioning
confidence: 99%